2019
DOI: 10.1002/ana.25476
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal course of vasomotor symptoms in perimenopausal migraineurs

Abstract: Objective: To examine the longitudinal course of vasomotor symptoms (VMS) in women with a history of migraine in comparison to women without a history of migraine disease. Methods: The study sample consisted of 467 women with a self-reported prior migraine diagnosis and 2,466 women without prior migraine diagnosis who were assessed longitudinally during menopausal transition as part of the Study of Women's Health Across the Nation. Linear mixed regression models with backward elimination were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(121 reference statements)
0
11
0
1
Order By: Relevance
“…A recent study using the SWAN cohort evaluated the presence of vasomotor symptoms in women with migraine over up to 10 years of follow-up [53]. This study found that a history of migraine predicted higher frequency of hot flashes and night sweats [53]. Overall, these studies support the notion that the prevalence and burden of migraine are most pronounced in perimenopause when hormonal imbalance is present, particularly in women with history of menstrual migraine.…”
Section: Migraine During the Menopausal Transitionmentioning
confidence: 57%
See 1 more Smart Citation
“…A recent study using the SWAN cohort evaluated the presence of vasomotor symptoms in women with migraine over up to 10 years of follow-up [53]. This study found that a history of migraine predicted higher frequency of hot flashes and night sweats [53]. Overall, these studies support the notion that the prevalence and burden of migraine are most pronounced in perimenopause when hormonal imbalance is present, particularly in women with history of menstrual migraine.…”
Section: Migraine During the Menopausal Transitionmentioning
confidence: 57%
“…Further, in cross-sectional studies, vasomotor symptoms have been reported to be more common among women with migraine [46]. A recent study using the SWAN cohort evaluated the presence of vasomotor symptoms in women with migraine over up to 10 years of follow-up [53]. This study found that a history of migraine predicted higher frequency of hot flashes and night sweats [53].…”
Section: Migraine During the Menopausal Transitionmentioning
confidence: 98%
“…Migraineurs were identified per self-report similar to previous reported studies in this population (12,19). Participants were asked if a doctor or any other health professional had diagnosed them with migraine headaches.…”
Section: Migraineurs and Controlsmentioning
confidence: 99%
“…In this study we hypothesized that women with migraine experience a significantly higher allostatic profile due to the added burden of frequent headaches and increased sleep disturbances during menopausal transition. This hypothesis is based on the burden of repeated migraine attacks as stressors (10, 11), the central role of the hypothalamically-mediated homeostasis (12) to the pathophysiology of migraine, and the significant modulatory influence of hormonal fluctuations during menopausal transition on the brain (13). Furthermore, since sleep disturbances have long been associated with migraines and other headache disorders (14), and sleep disorders are one of the main symptoms associated with menopausal transition (15)(16)(17), we hypothesized that sleep problems will have a modulatory influence on allostatic load and exacerbate it.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations and decline in the levels of ovarian hormones during this period also have significant modulatory influences on brain function (5255), which could have significant implications for neurological disorders, including migraine (56, 57). A recent study provides evidence for increased incidence of vasomotor symptoms in aging women with a history of migraine (58). This finding may be concordant with neuroimaging findings that have shown sex-specific and disease specific abnormalities in the structure and function of the insular cortex, the core cortical region for autonomic integration, in women with migraine.…”
Section: Sex Specific Traits In Migraineurs and Implications For Neurmentioning
confidence: 99%